The Bibliography of Józef Tadeusz Milik (1922–2006) - Klukowski, Michał (Verbum Vitae, 2023)
The bibliography is divided into five parts. The first part includes monographs and collective works authored by J. T. Milik and his contributions to various studies. The second one contains articles, chapters or entries in collective works; the third one contains his articles (both scientific and popular science) published in various periodicals or newspapers, while the fourth one includes Milik’s reviews. The last part of the bibliography is a supplement, which includes publications concerning the person and scientific activity of this eminent figure.